2021
DOI: 10.7717/peerj.11203
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis for the identification of differentially expressed genes and related signaling pathways in H. pylori-CagA transfected gastric cancer cells

Abstract: Aim Helicobacter pylori cytotoxin-associated protein A (CagA) is an important virulence factor known to induce gastric cancer development. However, the cause and the underlying molecular events of CagA induction remain unclear. Here, we applied integrated bioinformatics to identify the key genes involved in the process of CagA-induced gastric epithelial cell inflammation and can ceration to comprehend the potential molecular mechanisms involved. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…In previous research by our group, Hp-CagA transfected gastric cancer cells were used for transcriptome sequencing and it was found that the expression of FTO mRNA was increased (38). It was speculated that Hp may play a role in the development and progression of gastric cancer by increasing FTO expression.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research by our group, Hp-CagA transfected gastric cancer cells were used for transcriptome sequencing and it was found that the expression of FTO mRNA was increased (38). It was speculated that Hp may play a role in the development and progression of gastric cancer by increasing FTO expression.…”
Section: Discussionmentioning
confidence: 99%